The legal nature of contractor liability and scope of application in Iraqi civil law (An analytical study) - امىدرس امدكخِر صدكْ وحىدأؤي عٔسّ; امىدرس امىساعد طٍ حسي رسِل (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
There is no doubt that the contracting contract is one of the most important contracts in civil societies. It has been regulated in Iraqi legislation and comparative legislations within the range of named contracts, which does not necessarily mean that this contract has become known and does not require research and studies in many aspects . On the contrary, many of his subjects are in urgent need of modification, change or addition because the wheel of life does not stop , And in a continuous development, which requires the development of all aspects of civilian life, and this continuous development and rapid forces us to develop our legislation from time to time to keep pace with developments in the walks of life ,from here our study on the legal nature of the contractor's responsibility and the extent of its application in the Iraqi Civil Code . The first topic is devoted to the nature of the responsibility of the contractor in the Iraqi civil law divided into three demands, while the second topic deals with the scope of application of the provisions of the responsibility of the contractor and divided into three demands also, The research concluded with the most important conclusions and recommendations reached.